The perspective of social-medical disability model towards people with disabilities in the Malaysian context - Ferlis Bullare @ Bahari; Lineker Ak Takom; Rosnah Ismail; Mohd. Dahlan A. Malek; Jasmine Adela Mutang; Lailawati Madlan; Fariz A. Rani (2017)
In the medical model, disability is perceived as a chronic issue that may involve physical or mental disability which subsequently leads to the inability to work and be actively involved in society. Contrastingly, the social model perceives individuals with disability as minority group that suffers from discrimination, stigma, social alienation, repression, isolation and various social barriers which prohibit them to be well accepted by the society. However, the model that is suitable to be used in the Malaysian context still remain unanswered. This issue is crucial to be investigated because the medical model perspective has been lacking in the Malaysian community towards the disabled. Furthermore, it is also linked to capitalism and meritocracy which have been dominating the world community (McLaughlin and Kenji Kuno). The current study used the grounded theory method to explore and generate a disability concept according to the perspective of social and medical model towards individualswith disability in Malaysia. The grounded theory analysis yields five perspectives in the social-medical model, namely acceptance, independence, equity, accessibility and power to make decision, followed by three sources of social-medical model which include self-awareness towards individuals with disability, society awareness and parents awareness. The grounded theory also includes six barriers of social model, namely inequility, stigma, discrimination, barrier, isolation and ineffectiveness of the law, followed by two strategies involving the idea of getting support and getting knowledge) and finally, the influence of social-medical model (well-being). It is concluded that by determining and producing a new disability model from the existing social model and medical model, it could provide a valuable information especially to the government prior to the implementation of programs or policies.